First data on trace elements in Haliotis tuberculata (Linnaeus, 1758) from southern Italy: Safety issues. (July 2015) - Conte, Francesca; Copat, Chiara; Longo, Sabrina; Oliveri Conti, Gea; Grasso, Alfina; Arena, Giovanni; Brundo, Maria Violetta; Ferrante, Margherita
Highlights: The study provides first data on metals in Haliotis spp collected in southern Italy. Lead, Cd and Hg concentrations are lower than maximum levels set by CE Regulation. CT samples have significantly higher bioaccumulation levels. The EDI for each contaminant is lower than the provisional tolerable intake. THQ below 1 indicated no risk to develop chronic systemic effects due to metal intake. Abstract: This study evaluated for the first time the concentrations of 10 metals in wild specimens of abalone, Haliotis tuberculata (Ht) ( Linnaeus, 1758) from three sites along the southern Italian coast: Gulf of Catania (CT), the Northern Coast of Messina (ME) and the harbor of Villa San Giovanni (VSG). The species is commonly found in the area and has significant commercial value. Additionally, it is long lived, thus suitable as bioindicator of the environmental monitoring. The potential human health risks due to consumption of Ht have been assessed by estimated average daily intake (EDI) and target hazard quotient (THQ) of metals, respectively. In particular arsenic (As), cadmium (Cd), copper (Cu), chromium (Cr), iron (Fe), lead (Pb), manganese (Mn), mercury (Hg), selenium (Se) and vanadium (V) were quantified in the edible tissue of specimens by acid digestion of the samples and ICP-MS determination. The highest concentrations were found in CT sample area for most metals analyzed. Mean values for Pb, Cd and Hg were lower than the maximum levels (MLs) set for bivalve mollusks by Regulation (CE) no. 1881/2006 in all sites, and average intake values below the risk levels for human consumption.